Apparatus for measurements of transport properties of thin films under sulfur atmosphere at moderate temperatures. (16th March 2015) - Clamagirand, J M; Ares, J R; Diaz-Chao, P; Pascual, A; Ferrer, I J; Sánchez, C
Abstract: An experimental system able to simultaneously measure the electrical resistance and the thermopower of metallic and semiconducting thin films (with thicknesses from nm to µ m) under sulfur atmosphere from room temperature up to 400 °C and total pressures >0.5–1 mbar is designed and implemented. Calibration tests of the system were performed with palladium foils and films as well as p-type and n-type sulfide semiconducting films: iron disulfide and palladium monosulfide. Uncertainties of measured thermopower and resistance values are less than 10% and 5%, respectively. To check the capability of the system under sulfur atmosphere, in situ measurements of transport properties during sulfuration of palladium films were carried out. During the process, sulfur partial pressure and film temperature are accurately controlled. Apparatus may be used to determine the evolution of transport properties of different metal sulfides during their formation/decomposition processes, opening new pathways to investigate the thermoelectric properties of more complex thin film sulfides.